2014
DOI: 10.1063/1.4894077
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards the cold region or the hot region? Thermocapillary migration of a droplet attached on a horizontal substrate

Abstract: We study computationally thermocapillary migration of a two-dimensional droplet attached on a horizontal substrate with a constant temperature gradient. A level-set approach is employed to track the droplet interface and a Navier slip boundary condition is imposed to alleviate a stress singularity at the moving contact lines. The present numerical model allows us to consider droplets with large contact angles and to take into account effects of the fluid outside the droplet, both have not been well studied so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
2
24
1
Order By: Relevance
“…Thermocapillary flows can be computed by introducing the tangential surface tension force term into the CSF model in simulating multiphase systems . For instance, multiphase flow techniques (VOF, front tracking, and phase field) related to thermocapillary flow investigations include thermocapillary flow propulsion of bubbles (drops) , flow instability , and interface deformation by a thermocapillary flow in a cavity . Details can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Thermocapillary flows can be computed by introducing the tangential surface tension force term into the CSF model in simulating multiphase systems . For instance, multiphase flow techniques (VOF, front tracking, and phase field) related to thermocapillary flow investigations include thermocapillary flow propulsion of bubbles (drops) , flow instability , and interface deformation by a thermocapillary flow in a cavity . Details can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…We have confirmed that the phase diagram is robust when 0.5 Ma 40, and that the contact line moves in an opposite direction when using a cold instead of a hot wall. This flow diagram is surprisingly similar to that for the direction of thermocapillary translation of an entire droplet on a non-uniformly heated/cooled substrate (Sui 2014). In the subsequent subsections we investigate the origin of the spreading/dewetting reversal, not addressed in prior work.…”
Section: Dns Results For Moderate Contact Anglesmentioning
confidence: 68%
“…An explicit test from some asymptotic analysis is not available for the problem simulated though, due to differences in boundary conditions used in lubrication theory and the contact-line model in the simulations. A direct validation test for a non-isothermal system with contact lines has been conducted for another system, a cylindrical droplet on a substrate that is kept at a non-uniform temperature, see Sui (2014).…”
Section: Computational Methods For Dnsmentioning
confidence: 99%
“…An alternative approach would be to anticipate that the flow is indeed Marangoni and thus use the Marangoni velocity scale V M . [50][51][52]16,53 Here, it is most simply defined as…”
Section: Flow and Flow Regimementioning
confidence: 99%